Career evolution and knowledge of elite coaches of swimmers with a physical disability - Cregan, K.; Bloom, G. A.; Reid, G. (Research Quarterly for Exercise and Sport, 2007)
In the last decade there has been an increase in empirical research on coaches of elite able-bodied athletes, while coaches of athletes with a disability have generally been overlooked. Thus, the purpose of the current study was to address this oversight by examining the career evolution and knowledge of these coaches. Six elite coaches of swimmers with a physical disability were interviewed using an unstructured, open-ended interview format. Results revealed information pertaining to the coaches` backgrounds, career evolution, and knowledge in training and competition. As well, all coaches stressed the importance of coaching their athletes as an elite swimmer as opposed to coaching a swimmer with a disability.